Pengaruh Bantuan Modal Pengembangan Usaha Agribisnis Pedesaan (PUAP) Terhadap Kesejahteraan Petani Di Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung - Arti, Elsi Anggi; Juita, Erna; Zuriyani, Elvi (Pendidikan Geografi, 2013)
The implementation of developing agriculture, for most of the farmers, faced problem in financial capital and the access to the financial unstitutions. The ains of this ressarch is for finding out the effect of financial capital assistance toward the rural agribusiness enterprises development (PUAP) to the farmers prosperous life in Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung.Type of this research is correlasional descriptive research, which is located in Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung. The sample of this research were 100 farmers who got financial capital assitance of the rural agribusiness enterprises development (PUAP) in Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung. Free variable is financial capital and fostened variable is the farmers prosperous life.The result of this research found that the level of the financial capital of the rural agribusiness enterprises development which was gotten by the farmers in Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung was good 64,33%. The level of the farmers prosperous life in Kenagarian Tanjung Bonai Kecamatan Sumpur Kudus were good 65,33%, from the regression result was found that the financial capital assistance of the rural agribusiness enterprises development (PUAP) gave positive effect toword the farmers prosperous life in Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung 0,601 or 60,10%, and financial capital assistance (PUAP) have influenced the farmers prosperous life 0,700 or 70%. From t test result, it was found that the financial capital assistance (PUAP) gave significant effect to the farmers prosperous life in Kenagarian Tanjung Bonai Aur Kecamatan Sumpur Kudus Kabupaten Sijunjung, it was significant value 0,003.Â